Pembinaan Narapidana Pada Lembaga Pemasyarakatan Klas IIB Merauke : Lembaga Pemasyarakatan Klas IIB Meauke - Farida Romaito Pohan; Yohanes Budiman; Agus Siswanto (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2022)
Merauke Class IIB Penitentiary is an institution that follows up prisioners by providing then an education and skills for their future life after finish their prison term. This guidance program is very strategic in realizing the ultimate goal of the criminal justice system, namely the rehabilitation and resocialization of lawbreakers to crime prevention. The purpose of the study was to determine the role of the Class IIB Penitentiary Institution in fostering prisoners, the supporting and inhibiting factors, as well as what kind of coaching pattern was used. This study uses a qualitative method. The results of the study include: 1) The guidance given to inmates has the aim that prisoners can play an active role in development and can live normally as good and responsible citizens after their detention period is over. The guidance provided is adjusted to the talents and interests of the prisoners, so that the prisoners understand that all the guidance provided is for their own good, namely so that they have the readiness to return to society when they are released later; 2) Supporting factors in coaching for prisoners include a conducive situation, bottom-up approach coaching, adequate facilities and infrastructure, coaching is carried out in a family way, giving premiums or wages. Factors that hinder the efforts of Merauke Prison in developing skills for prisoners, namely supervisory officers who have not mastered the skills, limited marketing of the results of skills; 3) Establish cooperative relationships with third parties for the marketing of skills.